Looking to Learn Better - Training of Perception-Specific Focus of Attention Influences Quiet Eye Duration but Not Throwing Accuracy in Darts - Neugebauer, Judith; Baker, Joseph; Schorer, Jörg (Frontiers in Sports and Active Living, 2020)
Investigations of the association of focus of attention and quiet eye duration have shown mixed results. It is possible that when focusing on visuo-motor learning a more sensitive category system of instructions might be useful. The aim of this study was to investigate the interaction of focus of attention and quiet eye duration in darts. In addition to locus-directed foci (external, internal), perception-directed (visual, kinesthetic) foci of attention were considered. Participants were divided into four groups and had to perform a pre- and post-test with a one-week training intervention in between. Throwing accuracy (TA) and quiet eye duration (QED) were measured using the SMI eye tracking glasses. An analysis of covariance (2x2) showed no significant group differences or interactions for TA. For QED, an analysis of variance (2x2x2) showed quiet eye duration was increased with the intervention but there were significant differences between the tests. A significant interaction of test and perception-directed focus was observed. Visually instructed groups increased QED whereas the kinesthetic group decreased the QED, suggesting perceptual and motor learning may be asynchronous. One possible explanation for the trends might be the common-coding theory of perception and action.